2009
DOI: 10.1073/pnas.0906074106
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1,3 fucosyltransferases are master regulators of prostate cancer cell trafficking

Abstract: How cancer cells bind to vascular surfaces and extravasate into target organs is an underappreciated, yet essential step in metastasis. We postulate that the metastatic process involves discrete adhesive interactions between circulating cancer cells and microvascular endothelial cells. Sialyl Lewis X (sLe X ) on prostate cancer (PCa) cells is thought to promote metastasis by mediating PCa cell binding to microvascular endothelial (E)-selectin. Yet, regulation of sLe X and related E-selectin ligand expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 45 publications
5
118
0
Order By: Relevance
“…Recent studies have further demonstrated that expression of Fut7 is sufficient to confer E-selectin binding capacity to CD44. 39,40,54 In line with these findings, our expression analyses indicate that, compared with neutrophils, Th1 cells express very low levels of Fut4, whereas Fut7 expression is similar. This, together with the observation that cell arrest is differentially controlled by CD44 in Th1 cells and by ESL-1 in neutrophils ( 11 and this study), suggests a different repertoire of E-selectin ligands between these leukocyte subsets.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies have further demonstrated that expression of Fut7 is sufficient to confer E-selectin binding capacity to CD44. 39,40,54 In line with these findings, our expression analyses indicate that, compared with neutrophils, Th1 cells express very low levels of Fut4, whereas Fut7 expression is similar. This, together with the observation that cell arrest is differentially controlled by CD44 in Th1 cells and by ESL-1 in neutrophils ( 11 and this study), suggests a different repertoire of E-selectin ligands between these leukocyte subsets.…”
Section: Discussionsupporting
confidence: 73%
“…These fucosidases were down-regulated in PC3 cells, along with the up-regulation of Fut8 and Fut11 as observed in the global analysis, which explains the change in fucosylation observed in PC3 cells. In prostate tissues, three fucosyltransferases (FUT3, FUT6, and FUT7) have been shown to have elevated gene expression, and the overexpression of these fucosyltransferases in PC3 cells showed that they may serve as master regulators of prostate cancer cell trafficking and explain the aggressive nature of PC3 cells (31). In our global proteomic study, only two fucosyltransferases (FUT8 and FUT11) were identified as overexpressed in PC3 cells.…”
Section: Discussionmentioning
confidence: 84%
“…Notable in this regard is that genetic deficiencies in FUT activity lead to an inability to mount a robust inflammatory response (22). Furthermore, sLe X overexpressing tumors often exhibit increased transcription of ␣1, , and the increased expression of FUTs is linked to the metastatic ability of cancer cells (26,27). Consistent with ␣1,3-FUTs playing an important role in cancer, antisense-mediated decreases in FUTs, including FUT3, impair tumor growth (28) and limit metastasis (29).…”
mentioning
confidence: 81%